Immune triggers preceding neuralgic amyotrophy - Sparasci, Davide; Schilg‐Hafer, Lenka; Schreiner, Bettina; Scheidegger, Olivier; Peyer, Anne‐Kathrin; Lascano, Agustina Maria; Vicino, Alex; Décard, Bernhard Friedrich; Tsouni, Pinelopi; Humm, Andrea Monika; Pianezzi, Enea; Zezza, Giulia; et al. (European journal of neurology, 2024)
Background and purpose Infections and vaccinations have been identified as potential immunological triggers of neuralgic amyotrophy (NA), but the exact type and frequency of the preceding agents is unknown. Methods This was a multicentre, prospective, observational, matched case–control study. NA was diagnosed by neuromuscular experts according to validated clinical criteria and electrodiagnostic studies. Clinical data and biological samples of NA patients were collected within 90 days from disease onset between June 2018 and December 2023. All NA patients were asked about prior infection and vaccination in the month before disease onset. Serological tests for hepatitis E virus, human immunodeficiency virus, severe acute respiratory syndrome coronavirus 2, Epstein–Barr virus, cytomegalovirus, parvovirus B19, varicella‐zoster virus, Borrelia burgdorferi, Mycoplasma pneumoniae and Bartonella henselae were performed in a central laboratory. Each case was matched with a healthy control for age, sex, place of residence and time of blood collection. Results Fifty‐seven patients and corresponding controls were included. The mean age was 45 years for both groups. NA onset was preceded by a symptomatic infectious trigger confirmed by microbiological tests in 15/57 (26.3%) patients. Coronavirus disease 2019 vaccination was considered a potential trigger in 7/57 (12.3%) subjects. An acute viral infection was associated with a bilateral involvement of the brachial plexus (p = 0.003, Cramèr's V = 0.43). Conclusions Confirmed immune triggers (infection or vaccination) preceded disease onset in 22/57 (38.6%) NA cases. We suggest to test NA patients in the acute phase for intracellular antigens, especially in the case of concomitant bilateral involvement and hepatitis.